Simultaneous quantification of prodrug oseltamivir and its metabolite oseltamivir carboxylate in human plasma by LCâMS/MS to support a bioequivalence study - Ajay Gupta; Swati Guttikar; Pranav S. Shrivastav; Mallika Sanyal (Elsevier, 2013)
A simple, precise and rapid liquid chromatographyâtandem mass spectrometry (LCâMS/MS) method has been developed and validated for the simultaneous determination of oseltamivir and oseltamivir carboxylate, a neuraminidase inhibitor, using their deuterated analogs as internal standards (ISs). The method involved solid phase extraction of the analytes and ISs from 200Î¼L human plasma with no reconstitution and drying steps. The chromatographic separation was achieved on a Symmetry C18 (100mmÃ4.6mm, 5Î¼m) column using 10mM ammonium formate and acetonitrile (30:70, v/v) as the mobile phase in a run time of 2.0min. Quantitation of analytes and ISs were done by multiple reaction monitoring on a triple quadrupole mass spectrometer in the positive ionization mode. The linearity of the method was established in the concentration range of 0.5â200ng/mL and 2.0â800ng/mL for oseltamivir and oseltamivir carboxylate respectively. The mean extraction recovery for oseltamivir (94.4%) and oseltamivir carboxylate (92.7%) from spiked plasma samples was consistent and reproducible. The application of this method was demonstrated by a bioequivalence study in 42 healthy Indian subjects with 75mg oseltamivir phosphate capsules. The assay reproducibility was established by reanalysis of 151 incurred subject samples. Keywords: Oseltamivir, Oseltamivir carboxylate, LC-MS/MS, Human plasma, Bioequivalence study